YAP-TEAD1 control of cytoskeleton dynamics and intracellular tension guides human pluripotent stem cell mesoderm specification - Pagliari Stefania; Vinarsky Vladimir; Martino Fabiana; Perestrelo Ana Rubina; De La Cruz Jorge Oliver; Caluori Guido; Vrbsky Jan; Mozetic Pamela; Pompeiano Antonio; Zancla Andrea; Ranjani Sri Ganji; Skladal Petr; et al. (SPRINGERNATURE, 2022)
The tight regulation of cytoskeleton dynamics is required for a number of cellular processes, including migration, division and differentiation. YAP-TEAD respond to cell-cell interaction and to substrate mechanics and, among their downstream effects, prompt focal adhesion (FA) gene transcription, thus contributing to FA-cytoskeleton stability. This activity is key to the definition of adult cell mechanical properties and function. Its regulation and role in pluripotent stem cells are poorly understood. Human PSCs display a sustained basal YAP-driven transcriptional activity despite they grow in very dense colonies, indicating these cells are insensitive to contact inhibition. PSC inability to perceive cell-cell interactions can be restored by tampering with Tankyrase enzyme, thus favouring AMOT inhibition of YAP function. YAP-TEAD complex is promptly inactivated when germ layers are specified, and this event is needed to adjust PSC mechanical properties in response to physiological substrate stiffness. By providing evidence that YAP-TEAD1 complex targets key genes encoding for proteins involved in cytoskeleton dynamics, we suggest that substrate mechanics can direct PSC specification by influencing cytoskeleton arrangement and intracellular tension. We propose an aberrant activation of YAP-TEAD1 axis alters PSC potency by inhibiting cytoskeleton dynamics, thus paralyzing the changes in shape requested for the acquisition of the given phenotype.